2020
DOI: 10.1055/a-1122-8129
|View full text |Cite
|
Sign up to set email alerts
|

The Population Pharmacokinetics of Rifampicin in Japanese Pulmonary Tuberculosis Patients

Abstract: In Japan, tuberculosis has been recognized as one of the major infections requiring urgent measures because of its high morbidity rate even now especially in elderly people suffering from tuberculosis during the past epidemic and its reactivation. Hence, many Japanese clinicians have made efforts to suppress the onset of tuberculosis and treat it effectively. The objectives of this study are to (1) identify covariate(s) that may explain the variation of rifampicin, which is the key antitubercular agent, under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A combination of additive and proportional models for residual variability was described in 11 studies, 19,31,32,34,36,38,39,41,42,45,46 whereas an additive residual error model was reported in three studies 43,44,48 and a proportional model was recorded in four others 30,37,40,47 . Lastly, an exponential error model was implemented to quantify the interindividual variability in seven studies 31,35–37,39,43,49 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A combination of additive and proportional models for residual variability was described in 11 studies, 19,31,32,34,36,38,39,41,42,45,46 whereas an additive residual error model was reported in three studies 43,44,48 and a proportional model was recorded in four others 30,37,40,47 . Lastly, an exponential error model was implemented to quantify the interindividual variability in seven studies 31,35–37,39,43,49 …”
Section: Resultsmentioning
confidence: 99%
“…30,37,40,47 Lastly, an exponential error model was implemented to quantify the interindividual variability in seven studies. 31,[35][36][37]39,43,49 The finalised models were further evaluated via a basic internal validation approach (eg, goodness of fit), advanced internal validation (eg, bootstrapping, visual predictive check [VPC]) and external validation. In seven studies, a combination of VPC and bootstrapping was employed for model evaluation, 31,32,35,38,41,44,48 while a combination of goodness of fit and VPC was implemented in four studies.…”
Section: Population Pharmacokinetic Models and Model Evaluationmentioning
confidence: 99%
See 3 more Smart Citations